Optimal sensor placement for active control of floor vibration considering spillover effect associated with modal filtering. (15th June 2018) - Xue, Kai; Igarashi, Akira; Kachi, Takahiro
Highlights: An optimal sensor placement for active control of human-induced floor vibration is proposed. For application to floor impact noise reduction, use of the modal filtering technique and a PI phase compensator is assumed. The proposed method to determine sensor placement is based on a novel combination of the minimal spillover method and effective independence method. The test result proves effectiveness in application of active control of plate vibration. Abstract: Application of the modal filtering technique to active control can be effectively used to suppress vibration of floor panels by increasing the damping of the natural vibration modes involved. Limitation of this method is related to the spillover effect caused by the neglected modes. In this study, a sensor placement determination procedure is developed so that enhancement of the separation performance of the modeled modes and reduction of the spillover effect of the truncated modes in modal filtering are achieved at the same time by combining the minimum spillover method, effective independence method (EFI) and modal assurance criterion (MAC). Performance of the proposed procedure is investigated by conducting verification tests to control vibration of a rectangular steel plate with the modal filtering technique, and the sensor placement determined by the proposed approach achieves preferable results than other two sensor placement cases. The effectiveness of the proposed technique is also verified by state feedback control for individual modes. Using the proposed approach, effective active control of the steel plate vibration is successfully achieved.